Zasada państwa prawa w polskim systemie prawnym oraz konsekwencje jej naruszenia w prawie Unii Europejskiej - Serzhanova, Viktoria; Krzysztofik, Edyta (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The principle of the state of law is a significant value and foundation of the constitutions and political systems of contemporary democratic states. However, despite assuring its guarantees in the national legal order and the existing of the instruments enabling to control its observance, in case of the states characterized by weakly preserved democratic traditions the degree of its following can decrease. Therefore, international and supranational guarantees in this case are of a considerable importance. The hereby paper aims at analyzing the principle of the state of law conceptualized in the Polish basic law and the problems connected with the control of its observance in the EU.
Keywords: liability of the member-states; the principle of the democratic legal state; breaching the principle of the rule of law; the Constitution of the Republic of Poland; the control of observance; the state of law